Displaying knowledge through interrogatives in student-initiated sequences. Issue 1 (2nd January 2016) - Solem, Marit Skarbø
Abstract : This article presents an analysis of student initiatives in whole-class interactions. While prior research on question–answer sequences in classroom interactions has shown students to be rather passive recipients of knowledge, this article focuses on aspects of classroom interaction where students take a more active role. Following a conversation analytical approach to classroom interaction, this study investigates how students use interrogatives to initiate interactional sequences. The study draws on video recordings of 50 lessons, each about 45 min long, from three different upper secondary classrooms in Norway. It is argued that through the utterance design of the initiating interrogatives, the students present themselves as 'someone who knows something'. The initiating interrogatives display epistemic stance (e.g. Heritage 2012a, b) in different ways; consequently, the student-initiated interrogative sequences perform different types of actions, from requests for clarifications to potential corrections. Thus, the student-initiating sequences contribute to both the topical and interactional development of whole-class interactions. This study contributes to the research field of classroom interaction as it nuances the interactional and epistemic asymmetry of classroom interaction; it also investigates a less examined interactional structure in classrooms: the student-initiated sequence.